Analysis Of The Influence Of GRDP, Work Force And Total Population On Poverty Of North Sumatra Province, 2001-2020 - Malau, Pastriono; Rohana Panjaitan; Nathalin Tambunan; Riniati Simanihuruk; Indra Maipita (Outline Publisher, 2025)
The Poverty is a condition that has not been and has never been resolved on this earth. People who are still in poverty are still found in various countries, even in developed countries even though the phenomenon of poverty is a serious enough problem. The purpose of this study was to analyze the effect of Gross Regional Domestic Product (GRDPHB), Workforce, Population on Poverty in North Sumatra Province. The analysis used in this study is a multiple linear regression model, with secondary data for 2001-2020 obtained from the Central Bureau of Statistics (BPS) of North Sumatra. The results obtained from this study are: GRDP has a negative and significant effect on poverty in North Sumatra Province; Workforce has a positive and significant effect on poverty in North Sumatra Province; Total population has a positive and significant effect on poverty in North Sumatra Province. GRDP, Work Force, Total Population simultaneously have a significant effect on poverty in North Sumatra Province with a coefficient of determination of 92.62 percent. The most dominant variable influencing the poverty of North Sumatra Province is population size. Keywords : Poverty, Gross Regional Domestic Product, Labor Force, Total Population